Kemampuan Penurunan Kadar Kolesterol oleh Ekstrak Metanol Cinnamomum Burmanii Secara In Vitro - Zulfa, Lathifah Dzakiyyah; Salim, Dessyani; Natasha, Margaretha Maria Odilia; Sumilat, Lawrent Ernts; Djaya, Kevin Gilbert (Universitas Malahayati, 2024)
ABSTRACT Cholesterol is normally needed by human body as cell fluidity regulator, a precursor for the formation of steroid hormones, and precursor for the formation of bile acids, but excess cholesterol levels in the blood will increase the risk of cardiovascular disease. Some cholesterol lowering agents have side effects so exploration of herbal plants that can lower cholesterol levels is necessary. This study aims to prove the cholesterol binding ability of Cinnamomum burmanii methanol extract. In Vitro, through photometric measurements, cholesterol binding was carried out by the methanol extract of Cinnamomum burmanii. The absorbance value at the 526nm wave is then converted into a percentage of the reduction in cholesterol levels. The percentage of the reduction in cholesterol levels increased as the concentration of Cinnamomum burmanii methanol extract increased. The increasing percentage of reduction in cholesterol levels is based on the bonds formed from the contents of Cinnamomum burmanii, such as tannin and saponin. Keywords: Cholesterol, Cinnamomum Burmanii, ldl ABSTRAK Kolesterol secara normal dibutuhkan tubuh sebagai pengatur fluiditas sel, prekursor pembentukan hormon steroid, dan prekursor pembentukan asam empedu, namun kelebihan kadar kolesterol dalam darah akan meningkatkan risiko penyakit kardiovaskular. Beberapa agen penurun kadar kolesterol darah memiliki efek samping sehingga eksplorasi tanaman herbal yang mampu menurunkan kadar kolesterol diperlukan. Penelitian ini bertujuan untuk membuktikan kemampuan pengikatan kolesterol oleh ekstrak metanol kayu manis. Secara In Vitro melalui pengukuran fotometrik, dilakukan pengikatan kolesterol oleh ekstrak metanol Cinnamomum burmanii. Nilai absorbansi pada gelombang 526nm selanjutnya dikonversi menjadi persentase penurunan kadar kolesterol. Persentase penurunan kadar kolesterol bertambah tinggi seiring dengan bertambahnya konsentrasi ekstrak metanol kayu manis. Meningkatnya persetase penurunan kadar kolesterol didasari adanya ikatan yang terbentuk dari kandungan kayu manis, seperti tannin dan saponin. Kata Kunci: Ldl, Kayu Manis, Kolesterol